Impact of Direct Restorative Dental Materials on Surface Root Caries Treatment - Mohammad abdulrahman aldossari; Bader Mohammed almotairiy; Khalid Ibrahim Alanazi; Yazeed sultan Alsabeh; Khalid Mohammed Faqihi; Musab Jurayyad Aljurayyad; Abdullah Saeed Albaqami; Bader Saad Aldobaian; Abdulhmeed abdulmohsen alodib; Sakhar Fahad Almuhaya (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Root caries management is essential for tooth preservation. Direct restorative materials like resin-modified GIC, glass ionomer cement (GIC), and composite resins are used for their cariostatic properties and mineralization potential. Aim: This meta-analysis study aimed to assess the efficacy of direct restorative materials in the therapy of surface root caries. Methods: A search of PubMed, Embase, Cochrane Library, and Google Scholar identified studies on root caries, restorative materials, remineralization, and mineral density. Additional searches were done on ClinicalTrials.gov and relevant references were reviewed. Results: The meta-analysis identified 412 studies, with five meeting the inclusion criteria for analysis. These studies focused on evaluating the impact of various restorative materials on mineral profiles, outer lesion depth, and cariostatic efficacy. Key findings include the high remineralization and mineral density retention provided by GIC, especially when modified with SDF or CPP-ACP. SEM and FTIR analyses showed that these materials improved mineral composition and reduced organic matrix exposure at the restoration interface, demonstrating their potential in managing root caries effectively. Conclusion: GIC and its modified forms, particularly with SDF or CPP-ACP, effectively prevent mineral loss, enhance remineralization, and reduce lesion depth. These materials show promise in root caries management, though more clinical investigations are needed to confirm long-term efficiency.